The Impact of Preference Erosionon Middle-Income Developing Countries - Lankes, Hans.; Alexandraki, Katerina (Washington, D.C. : International Monetary Fund, 2004)
Preference erosion has become an obstacle to multilateral trade liberalization, as beneficiaries of trade preferences have an incentive to resist reductions in mostfavored- nation (MFN) tariffs. This study identifies middle-income developing countries that are vulnerable to export revenue loss from preference erosion. It concludes that the problem is heavily concentrated in a sub-set of preference beneficiaries-primarily small island economies dependent on sugar, banana, and-to a lesser extent-textile exports. Accordingly, measures to help mitigate the impact of preference erosion can be closely targeted at the countries at risk.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet